Combined Metabolome and Transcriptome Analyses Reveal the Flavonoids Changes and Biosynthesis Mechanisms in Different Organs of Hibiseu manihot L. - Zhou, Yuhan; Xu, Xiaodi; Chen, Yanzhu; Gao, Jun; Shi, Qiyu; Tian, Liang; Cao, Li (Frontiers in Plant Science, 2022)
Hibiseu manihot L. (Jinhuakui, JHK) is widely cultivated as a landscape plant, with pharmacological effects due to its high flavonoids content, which is also known as a garden landscape plant. Although flavonoids were the main active pharmaceutical ingredients in JHK, little information was obtained about the content, composition, and accumulation pattern of flavonoids in different tissues. Most studies only identified a few kinds of flavonoids in JHK limited by separation and identification problems. Therefore, combined metabolome and transcriptome analysis was performed to explore the accumulation patterns and biosynthesis mechanisms of flavonoids in JHK. In this study, we identified 160 flavonoids in 15 samples of JHK (flower, leaf, root, stem, and seeds) by using LC-MS/MS. Consistent with the total flavonoid content determination, these flavonoids were significantly accumulated in flowers, followed by leaves, stems, roots, and seeds. Among them, certain flavonoids, with high content, were also identified for the first time in JHK, such as tricetin, catechin, hesperidin, ncyanidin-3-O-sambubioside, astragalin, procyanidin B2/B3/C1, and apigenin-5-O-glucoside, etc. Different tissues underwent significantly reprogramming of their transcriptomes and metabolites changes in JHK, particularly in the flavonoid, flavone, and flavonol biosynthesis pathways. We conducted a correlation analysis between RNA-Seq and LC-MS/MS to identify the key genes and related flavonoids compounds and rebuild the gene-metabolites regulatory sub-networks, and then identified 15 key genes highly related to flavonoids accumulation in JHK. These key genes might play a fine regulatory role in flavonoids biosynthesis by affecting the gene expression level in different organs of JHK. Our results could be helpful for the improvement of the market/industrial utilization value of different parts of JHK, and to pave the way for the regulatory mechanism research of flavonoids biosynthesis, and provide insight for studying the production quality improvement of JHK.